Covering Galas And Batu Sapi By-elections: Framing By Chinese Newspapers - Ishak, Md. Sidin Ahmad; Yang , Lai Fong (Penerbit Universiti Sains Malaysia (USM Press), 2013)
In this article, the authors report the outcome of a thorough analysis of how Malaysian Chinese newspapers—Sin Chew Daily and Nanyang Siang Pau— reported the two last Malaysian by-elections in 2010, which are the Galas and Batu Sapi by-elections. These two by-elections were important because their results were considered as significant indications of the people's confidence in the ruling coalition and the Prime Minister Najib's promises to reform since the political tsunami in 2008. The outcomes of these two by-elections were also seemed as indications of the people's voting pattern for the upcoming 13th Malaysian general election, which must be held by 2013.